Epidemiology, pathology, prevention, and control strategies of inclusion body hepatitis and hepatitis-hydropericardium syndrome in poultry: A comprehensive review - El-Shall, Nahed A.; El-Hamid, Hatem S. Abd; Elkady, Magdy F.; Ellakany, Hany F.; Elbestawy, Ahmed R.; Gado, Ahmed R.; Geneedy, Amr M.; Hasan, Mohamed E.; Jaremko, Mariusz; Selim, Samy; El-Tarabily, Khaled A.; El-Hack, Mohamed E. Abd (Frontiers in Veterinary Science, 2022)
Fowl adenoviruses (FAdVs) infection can cause a variety of syndromes in poultry production, such as inclusion body hepatitis (IBH), hepatitis-hydropericardium syndrome (HHS), and others, resulting in massive economic losses worldwide. FAdVs are classified into five species (A to E) and 12 serotypes (1 to 8a and 8b to 11). FAdV strains are found all over the world, and the majority of avian species are susceptible to infection. Both IBH and HHS are caused by the Aviadenovirus genus, which is part of the Adenoviridae family. Vertical, horizontal, and mechanical transmissions are the most common modes of transmission. IBH is distinguished by hepatitis with basophilic intranuclear inclusion bodies, whereas HHS is distinguished by the accumulation of transparent or straw-colored fluid in the pericardial sac in addition to hepatitis. Confirmatory diagnosis of IBH and HHS is critical because the clinical signs and postmortem lesions are not specific to their syndromes. The detection of specific lesions and inclusion bodies under the microscope may be indicative. Traditional viral isolation in tissue culture of avian origin is more sensitive than embryonated avian eggs. In addition, molecular diagnostic techniques are now widely used for the rapid and accurate detection of Aviadenovirus. To protect progenies, prevention strategies should rely on effective biosecurity measures, as well as vaccination of breeders before production. This review provides an overview of the current global and local situation of IBH and HHS (FAdVs) and explains their problems and vaccination strategies.